Peningkatan Kapasitas Bisnis Sampah Rumah Tangga Pada Kelompok Bank Sampah Tunas Sejahtera Kota Blitar - Puspitorini, Palupi; Purwatiningsih, Rini; Sunandes, Aris (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Since the establishment of the Sustainable Development Goals (SDGs) in 2015, sustainability issues in the economic and social sectors have gained significant attention. The Indonesian government is committed to restoring the national economy to a better state than before the pandemic by transitioning towards a green or circular economy. The circular economy aims to maximize the utility and added value of raw materials, components, and products to reduce waste. According to the 2022 data from the National Waste Management Information System (SIPSN), 34.29% (7.2 million tons) of the 21.1 million tons of national waste remain unmanaged. Collaborative efforts between central and regional governments continue to implement effective waste management policies based on circular economy principles. The methods employed in this program include training and mentoring in processing organic and inorganic waste into marketable products, information management training, business management enhancement, human resources training, and collaboration with other waste banks. The results indicate an increase in the production capacity of the Tunas Sejahtera Waste Bank from 300 kg to 1 ton per month. Training in management and marketing has also improved operational efficiency and expanded market reach, thereby increasing revenue and enhancing the circular economy's impact